Comprehensive multi-omics analysis of tandem duplicator phenotypes in non-small cell lung cancer - Li, Jie; Pan, Xinyan; Bi, Yanting; Huang, Jian; Peng, Jun; Bai, ChunLing; Hou, Jianhong; Chen, Yang (Frontiers in Medicine, 2025)
IntroductionThe Tandem Duplicator Phenotype (TDP) is a prominent genomic metric prevalent in non-small cell lung cancer (NSCLC).MethodsMulti-omics samples including DNA copy number, transcriptomics, somatic single-nucleotide variations, clinical data, and cell-line drug sensitivity from TCGA and CCLE are delved into TDP characteristics.ResultsOur thorough analysis reveals that patients with smaller span sizes TDP have a more intricate genome, moderate pathology, enhanced therapeutic response, favorable prognosis, a more active immune system, and higher drug sensitivity. In contrast, those with larger span sizes TDP exhibited opposite trends.DiscussionThe integrated analysis underscores that an in-depth molecular assessment of TDP can offer invaluable insights into its role in cancers. Classification strategy of TDP could recognize the chemotherapy sensitivity of different NSCLC patients.